Corporate Social Responsibility and Corporate Governance: A Bibliometric Analysis Study - Ervina Dian Ayu Kencana; Arni Surwanti (Green Publisher Indonesia, 2026)
The intersection of Corporate Social Responsibility (CSR) and Corporate Governance (CG) has become a central theme in academic discourse, reflecting the growing demand for corporate accountability and sustainability. This study aims to map the intellectual landscape and trace the evolution of research at the nexus of CSR and CG through a bibliometric approach. Data were sourced from the Scopus database, and after filtering for English-language articles, a final dataset of 1,530 documents published between 2015 and 2024 was analyzed. The bibliometric analysis encompasses annual publication trends, the identification of the most influential authors and highly cited articles, and a multi-faceted visualization of the research field using VOSviewer. This includes network analysis to map thematic clusters, overlay visualization to reveal the temporal evolution of topics, and density visualization to identify core and emerging research themes. VOSviewer visualizations uncover a robust and evolving relationship between CSR and CG, structured around five primary thematic clusters: corporate governance and board diversity, ESG and environmental performance, CSR disclosure and firm performance, financial performance and firm value, and contemporary issues such as the COVID-19 pandemic. The study not only charts the developmental trajectory of this scientific discourse but also provides a solid foundation for identifying future research directions that are pertinent to contemporary challenges